2016
DOI: 10.1002/adma.201602900
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Surfaces through Sequential Stop‐Flow Photopatterning

Abstract: Solution-exchange lithography is a new modular approach to engineer surfaces via sequential photopatterning. An array of lenses reduces features on an inkjet-printed photomask and reproduces arbitrarily complex patterns onto surfaces. In situ exchange of solutions allows successive photochemical reactions without moving the substrate and affords access to hierarchically patterned substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 50 publications
(86 reference statements)
0
82
0
Order By: Relevance
“…), a reducing organic photoredox catalyst—10‐phenylphenothiazine (PTH)—has been developed for the light‐mediated removal of halogen chain‐ends from styrenic, acrylic and methacrylic polymers . This quantitative method is readily applicable to thin films, enabling the facile preparation of hierarchical patterned polymer brush films …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), a reducing organic photoredox catalyst—10‐phenylphenothiazine (PTH)—has been developed for the light‐mediated removal of halogen chain‐ends from styrenic, acrylic and methacrylic polymers . This quantitative method is readily applicable to thin films, enabling the facile preparation of hierarchical patterned polymer brush films …”
Section: Discussionmentioning
confidence: 99%
“… Transferal of small molecule organic chemistry for the chain‐end modification of polymers. Photochemical dehalogenation of polymers, and polymer brush surfaces using PTH. Typical reaction conditions: 5 mol% PTH, HCOOH (5 equiv.)…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the thermal reactions described by Hayashi and Studer, we have found that the synthesis of n‐type CPs requires photochemical conditions. Photopolymerizations offer the opportunity for spatiotemporal control and selective catalyst activation by different wavelengths of light . For non‐conjugated polymers, researchers have developed a range of photocontrolled polymerizations .…”
Section: Introductionmentioning
confidence: 99%
“…conditions.P hotopolymerizations offer the opportunity for spatiotemporal control [16][17][18] and selective catalyst activation by different wavelengths of light. [19][20][21] Forn on-conjugated polymers,r esearchers have developed ar ange of photocontrolled polymerizations.…”
mentioning
confidence: 99%
“…30,31 In particular, surface initiated atom transfer radical polymerization (SI-ATRP) catalyzed by photoactive Ir(III) phosphors can be used to pattern polymer brushes using visible light, 32 and the “living” nature of this process permits hierarchical patterning of block copolymer brush architectures with submicron feature resolution. 26 …”
Section: Introductionmentioning
confidence: 99%